Analisis Sistem Tanggap Darurat Kebakaran APAR di Kantor Pusat Perusahaan SDM - Riyandi Huda Mareda; Yusuf Faiqul Ilmi; Muhammad Rafli Cahyadi Putra; Moch Luqman Ashari (Pusat Riset dan Inovasi Nasional, 2023)
Fire is a serious threat that can cause huge losses, both in terms of loss of life and property damage. Therefore, it is important to have an effective and reliable fire suppression system in place. This article aims to explain the APAR (Light Fire Extinguisher) fire extinguishing system used in the Bussines Office